STUDENT'S CRITICAL THINKING SKILL ON BIOLOGY LEARNING THROUGH THE IMPLEMENTATION OF ACCELERATED LEARNING A CASE STUDY OF X GRADE STUDENTS SMA NEGERI KARANGPANDAN KARANGANYAR - Puguh Karyanto, Asih Fitriani, Meti Indrowati (Pendidikan Biologi, 2015)
The aim of study is to know the student's critical thinking skill on biology learning through the implementation of accelerated learning of x grade students of SMA Negeri Karangpandan. Karanganyar. The purpose of this research is motivated by the implementation of the biological learning process that has not been able to take an active role in student learning. This cause the students do not understand in understanding biological materials so that learning objectives are not achieved. Students tend to be passive and could not pull out his mind freely. Alternative approaches that can improve critical thinking skills of the students' are using Accelerated Learning (AL).The research included in the quasi-experimental research design using post-test and Non Equivalent Control Group Design. This study uses a Accelerated Learning in the experimental group and the deductive approach with the method of discussion, lecture and question and answer in the control group. The study population was all students of class X SMA Karangpandan. Karanganyar academic year 2012/2013. Sampling technique with cluster sampling. Data collection techniques using test and non-test methods. The description of the methods of non-test methods and test using the documentation and observation. Hypothesis test using t-test.The conclusions of this study approached AL significantly affect skills students in critical thinking in class X SMA Karangpandan. AL accommodate many learning elements that can make learning fun so excited and learning process better. Joyful learning can assist students in developing critical thinking skills. Key Words: approach to accelerate learning, critical thinking skills.